Schizorhodopsins: A family of rhodopsins from Asgard archaea that function as light-driven inward H(+) pumps - Inoue, Keiichi (Sci Adv, 2020)
Schizorhodopsins (SzRs), a rhodopsin family first identified in Asgard archaea, the archaeal group closest to eukaryotes, are present at a phylogenetically intermediate position between typical microbial rhodopsins and heliorhodopsins. However, the biological function and molecular properties of SzRs have not been reported. Here, SzRs from Asgardarchaeota and from a yet unknown microorganism are expressed in Escherichia coli and mammalian cells, and ion transport assays and patch clamp analyses are used to demonstrate SzR as a novel type of light-driven inward H(+) pump. The mutation of a cytoplasmic glutamate inhibited inward H(+) transport, suggesting that it functions as a cytoplasmic H(+) acceptor. The function, trimeric structure, and H(+) transport mechanism of SzR are similar to that of xenorhodopsin (XeR), a light-driven inward H(+) pumping microbial rhodopsins, implying that they evolved convergently. The inward H(+) pump function of SzR provides new insight into the photobiological life cycle of the Asgardarchaeota.